The results of epidemiological effectiveness study of Jodantipyrin as a drug for immediate prophylaxis of tick-borne encephalitis - V. N. Khudolei; Ye. V. Zamyatina; Ye. A. Kropotkina; L. V. Lukashova; A. V. Lepyokhin; G. A. Danchinova; V. I. Zlobin (Бюллетень сибирской медицины)
Jodantipyrin is an antiviral medicament, inductor of endogenous interferon. It relates to the group of nonsteroidal antiinflammatory medicaments of pyrazolone derivative. The principal mechanism of Jodantipyrin antiviral effect is its ability to induce endogenous interferons of the 1 st and 2 nd types, what has been confirmed by the results of numerous and detailed preclinical and clinical trials. At the present time a long-term experience of this medicament application as a prophylactic agent in case of tick-borne encephalitis and data of postmarketing monitoring of the medicament safety have been accumulated. This experience confirms efficacy of the medicament in prophylaxis of tick-borne encephalitis.